On the Design of Data Sets for Forecasting with Dynamic Factor Models - Gerhard Rünstler (Austrian Institute of Economic Research (WIFO), 2010)
Forecasts from dynamic factor models potentially benefit from refining the data set by eliminating uninformative series. The paper proposes to use forecast weights as provided by the factor model itself for this purpose. Monte Carlo simulations and an empirical application to forecasting euro area, German, and French GDP growth from unbalanced monthly data suggest that both forecast weights and least angle regressions result in improved forecasts. Overall, forecast weights provide yet more robust results.
Keywords: 330; Faktorenanalyse; Prognoseverfahren; Monte-Carlo-Simulation; Schätzung; Nationaleinkommen; Deutschland; Frankreich